1998
DOI: 10.1074/jbc.273.1.518
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Phage T4 PinA Protein, an Inhibitor of the ATP-dependent Lon Protease ofEscherichia coli

Abstract: The bacteriophage T4 PinA protein, expression of which leads to inhibition of protein degradation in Escherichia coli cells, has been purified from cells carrying multiple copies of the pinA gene. PinA is a heat-stable protein with a subunit M r of 18,800 and an isoelectric point of 4.6. Under nondenaturing conditions on a gel filtration column, PinA migrated in two peaks corresponding to a dimer and a tetramer. Purified PinA inhibited ATP-dependent protein degradation by Lon protease in vitro; it did not inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…For example, unfolded casein stimulates both the ATPase and peptidase activity of Lon by interacting with an allosteric protein-binding site on Lon (82)(83)(84). In addition, the bacteriophage T4 PinA protein specifically inhibits E. coli Lon but not ClpAP or HslUV (ClpYQ) (82). PinA does not interact with the ATP-binding site, the proteolytic active site or the allosteric protein-binding site of Lon.…”
Section: Modulation Of Lon Protease Activity In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…For example, unfolded casein stimulates both the ATPase and peptidase activity of Lon by interacting with an allosteric protein-binding site on Lon (82)(83)(84). In addition, the bacteriophage T4 PinA protein specifically inhibits E. coli Lon but not ClpAP or HslUV (ClpYQ) (82). PinA does not interact with the ATP-binding site, the proteolytic active site or the allosteric protein-binding site of Lon.…”
Section: Modulation Of Lon Protease Activity In Vivomentioning
confidence: 99%
“…Unfolded protein substrates have been shown to stimulate both the peptidase and ATPase activities of Lon (2,81). For example, unfolded casein stimulates both the ATPase and peptidase activity of Lon by interacting with an allosteric protein-binding site on Lon (82)(83)(84). In addition, the bacteriophage T4 PinA protein specifically inhibits E. coli Lon but not ClpAP or HslUV (ClpYQ) (82).…”
Section: Modulation Of Lon Protease Activity In Vivomentioning
confidence: 99%
“…PinA and Lon, assay for casein degradation, buffer composition, and methods for SDS-PAGE 1 and gel filtration were described in the preceding paper (13). An ATP-regenerating system consisting of 50 mM creatine phosphate and 20 g/ml phosphocreatine kinase was used in some assays.…”
Section: Purification Procedures and Standard Methods-the Purificatiomentioning
confidence: 99%
“…Our previous data showed that a dimer of PinA binds to a tetramer of Lon (13). Lon has four potential ATPase sites per tetramer, and inhibition of all stimulated ATPase activity by a single PinA dimer implies that Lon subunits act in a cooperative manner.…”
Section: Pina Effects On Peptidase Activity Of Lonmentioning
confidence: 99%
See 1 more Smart Citation